Langerhans Cell Histocytosis in Cervical Spine: A Rare Case Report - Karki, Mohan; Roka, Yam; Pandey, Sagar Raj (Nepal Journal of Neuroscience, 2023)
Langerhans cell histocytosis (LCH) in spine is a benign disorder that rare in adults and mainly affects children. We report the case of a 16 year-male presented to us with severe pain in nape region and upper limb radiculopathy along with upper limbs weakness for 4 months. He had history of fall injury 6month ago. Radiological investigation revealed to have a solitary osteolytic lesion with pathological fracture at C6 vertebral body. MRI showed hyper intense lesion in T2 sagittal images and hyper intense in T1 sagittal images in C6 vertebral body. The patient underwent surgical management in the form of excision of lesion, anterior C6 Corpectomy with C5-C6, C6-C7 discetomy and reconstruction with titanium cage and plating. Patient had immediate relief of nape region pain and radiculopathy. The accurate diagnosis of LCH was founded on histological examination.